History of Karras Colony and Nearby Settlements of Europeans in 19th — First Half of 20th Centuries at Present Stage of Study - V. A. Fomenko; A. T. Dzhumagulova (Научный диалог, 2021)
The issues of the current stage of studying the history of the Karras colony and nearby European settlements in the 19th and first half of the 20th centuries are considered. A review and analysis of new sources and historiography from 2000 to 2020 has been carried out. The relevance of the study is due to the poorly studied and fragmentary coverage of the history of European settlements in the central part of the North Caucasus in the 19th — first half of the 20th centuries in Russian historiography. The authors dwell on terminology issues. It is emphasized that the terms-cliches ‘mountaineers’ and ‘Tatars’ are characteristic of the historical literature of the 19th century and are inaccurately used by some authors today. The novelty of the research is seen in the fact that in this work the history of the Karras colony and neighboring settlements of Europeans in the 19th — first half of the 20th centuries is considered based on publications of 2000—2020. It is concluded that there is a possibility and a need for an independent review of the history of the Scottish mission, the center of which was originally located in Karras. The authors proceed from the fact that the history of the settlements of the colonists has a broader chronological framework and the main task of the colonists was not always missionary activity.